THE ROLE OF EMOTION REGULATION, STRESS, AND BINGE EATING IN WOMEN WITH POLYCYSTIC OVARY SYNDROME (PCOS) - Tarim Nayab; Dr Shammem Akhter, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
The present study was planned to explore the relationship between emotion regulation, stress and binge eating in women with Polycystic Ovary Syndrome (PCOS). Understanding how these specific variables contribute to the development and exacerbation of Polycystic Ovary Syndrome in women can provide valuable insights for prevention strategies. To collect the data from participants, the sample size was (N=100) women with Polycystic Ovary syndrome women were recruited to participate in the current study. The sample size was determined by analyzing the previous research (Khan et al., 2024). The one hundred participants were selected through Purposive sampling technique and ccorrelational research design was used. The scales Emotion Regulation Questionnaire (Gullone & Taffe., 2011), Stress Scale (Cohen et al., 1988) and Binge Eating Scale (Gormally et al., 1982) were used to measure the study variables. Results on correlational analysis affirmed that in women with polycystic ovary syndrome, there is a positive correlation between perceived stress and binge eating in women with PCOS. On the other hand, there is a negative correlation between emotion regulation and binge eating. Findings indicates that higher stress level can cause binge eating in women who have PCOS. Further results demonstrate that emotion regulation is not the reason to cause binge eating in women with PCOS. Current research reinforces the understanding that PCOS is not only a physiological disorder but also one with substantial psychological and behavioral dimensions. Women with PCOS often face significant emotional challenges, including stress anxiety depression which negatively impact their body image and self-worth.https://doi.org/10.5281/zenodo.13236899